Digitalisasi Karya TGKH. Muhammad Zainuddin Abdul Madjid berbasis mobile sebagai media pembelajaran interaktif untuk pelestarian peninggalan pendiri Nahdlatul Wathan - Hariman Bahtiar; Muhamad Wasil; Bambang Harianto (Infotek: Jurnal Informatika dan Teknologi, 2019)
ABSTRACTTGKH. Muhammad Zainuddin Abdul Madjid is a charismatic scholar on the island of Lombok and is the founder of Nahdlatul Wathan, the largest organization in West Nusa Tenggara. The works of Maulana Shaykh TGKH. Muhammad Zainuddin Abdul Madjid, like his books is a practice that routines are read by students and santriwati even the Nahdlatul Wathan congregation, as prayers and lessons that are practiced every time they finish worship and at critical times. Maulana Shaykh TGKH. Muhammad Zainuddin Abdul Madjid has many santri and santriwati in West Nusa Tenggara, even the archipelago under the Nahdlatul Wathan organization who faithfully practice his teachings and even his advice. Problems arise when his students are constrained by distance and time who want to read the books of his teacher. Therefore the author provides a solution with the Digitization of TGKH Works. Muhammad Zainuddin Abdul Madjid is based on mobile as an interactive learning medium for the preservation of the legacy of the founder of Nahdlatul Wathan. That will help his students who in fact do not have the book and are hindered by distance and time. Work begins with typing the contents of the book, followed by the implementation of the application, and in the end the application can be further utilizedDOI : 10.29408/jit.v2i1.940